O marco do Cariri: documentário biográfico sobre os caminhos culturais traçados pelo artista popular Marco di Aurélio - Pereira, Niutildes Batista (2022)
This Critical-Reflective Report describes the steps taken in the elaboration of the biographical documentary “O MARCO DO CARIRI”, which addresses the life story of Marco di Aurélio, a relevant person from Pernambuco in the culture of Paraíba, making connections between his personal memories to the present, highlighting the identity of the cariri in Paraíba where he has been carrying out artistic works that stimulate local popular artists. The documentary is an overview of his performances related to folkcommunication, precisely with the concept of media activists, where it highlights Marco di Aurélio's active relationship in his life trajectory, with popular culture and the universe of communication. Through the life story, journalistic resources such as in-depth interviews and participant observation were used in the documentary production stages, to present this popular character. For that, we base ourselves on authors Beltrão (1980), Melo (2008), Trigueiro (2008), Schmidt (2015), Lima (1995), Nichols (2005), Lucena (2012), Duarte (2005), Medina (2006) and Bezerra (2014). The documentary “O MARCO DO CARIRI: Biographical Documentary about the cultural paths traced by the popular artist Marco di Aurélio” brings to the center of the discussion, popular culture, the dilemmas of an artist and his correlation, as a cultural activist, with other artists to keep a tradition alive. A message of struggle, resistance and respect for the memory of the people of Cariri Paraíba, showing through the performance of the character Marco di Aurélio, the cultural context of the region inserted in social media by its audiovisual records. Link https://youtu.be/ZeTlOjYNd-M.